Just‐in‐time rescue plerixafor in combination with chemotherapy and granulocyte‐colony stimulating factor for peripheral blood progenitor cell mobilization. Issue 9 (23rd July 2013) - Smith, Veronica R.; Popat, Uday; Ciurea, Stefan; Nieto, Yago; Anderlini, Paolo; Rondon, Gabriela; Alousi, Amin; Qazilbash, Muzaffar; Kebriaei, Partow; Khouri, Issa; de, Marcos; Champlin, Richard; et al.
<x xml:space="preserve">Abstract</x> Plerixafor, a recently approved peripheral blood progenitor cell mobilizing agent, is often added to granulocyte‐colony stimulating factor (G‐CSF) to mobilize peripheral blood progenitor cells in patients with lymphoma or myeloma who cannot mobilize enough CD34+ cells with G‐CSF alone to undergo autologous stem cell transplantation. However, data are lacking regarding the feasibility and efficacy of just‐in‐time plerixafor in combination with chemotherapy and G‐CSF. We reviewed the peripheral blood stem cell collection data of 38 consecutive patients with lymphoma (Hodgkin's and non‐Hodgkin's) and multiple myeloma who underwent chemomobilization and high‐dose G‐CSF and just‐in‐time plerixafor to evaluate the efficacy of this treatment combination. All patients with multiple myeloma and all but one patient with lymphoma collected the minimum required number of CD34+ cells to proceed with autologous stem cell transplantation (>2 × 106/kg of body weight). The median CD34+ cell dose collected in patients with non‐Hodgkin lymphoma was 4.93 × 106/kg of body weight. The median CD34+ cell dose collected for patients with multiple myeloma was 8.81 × 106/kg of body weight. Plerixafor was well tolerated; no grade 2 or higher non‐hematologic toxic effects were observed. Am. J. Hematol. 88:754–757, 2013. © 2013 Wiley Periodicals, Inc.